To eliminate the y-terms and solve for x in the fewest steps, by which constants should the equations be multiplied by before ad ding the equations together? First Equation: 5x − 4y = 28 Second equation: 3x - 9y = 30
2 answers:
Answer:
The first equation should be multiplied by 9 and the second equation by −4.
Step-by-step explanation:
Answer:
use -9 to multiply the first equation
use -4 to multiply the second equation.
Step-by-step explanation:
5x-4y=28.....eqn (1)×-9
3x-9y=30....eqn(2)×-4
-45x+36y=-252
-(-12x+36y=-120)
therefore, -33x÷33 =-132÷-33
x=4.
substitute (x=4) in any of the equation. I'm just going to use eqn 1.
5x-4y=28
5(4)-4y=28
20-4y=28
-4y =28-20
-4y÷-4 = 8÷-4
y=-2
so, x=4, y=-2
Note: for proof of answers substitute the answers for x and y and see if you have the same result...e.g
5(4)-4(-2)=28.
You might be interested in
The answers once compounded equals $65068.44. Hope this helps:)
Answer:
1/12
Step-by-step explanation:
When you are doing probability with multiple things at once you have to multiply the probabilities of each asked number from each object together to get the probability of them both landing on those numbers
Answer:
2(10x10x10)
Step-by-step explanation:
Your answer should be C. 3x^3√2
Answer:
4,331.25 in interest
Step-by-step explanation:
22,500.00x3.5%=787.50x5.5=4,331.25
22,500.00+4,331.25=26,831.25 total loan